2014
DOI: 10.2478/s13382-014-0234-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes in workers exposed to fine particulate dust

Abstract: Objectives: Epidemiological studies provide evidence that airborne particulate matter may contribute to the increased incidence and mortality rates due to pulmonary and cardiovascular diseases. Only some of them address the problem of occupational exposure to particulate air pollution. The aim of our study was to assess cardiovascular reaction and autonomic regulation in workers exposed to fine particles. Materials and Methods: All workers had medical examination, resting ECG with heart rate variability analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Their ability to harbour environmental or workplace contaminants allows them to act as potential carriers of toxic or carcinogenic agents, such as polyaromatic hydrocarbons (PAHs) and per-and poly-fluoroalkyl substances, into the human airway and lung [11,20]. Once in the lungs, the particles and their contaminants can induce disease processes, resulting in pathophysiological changes that disrupt normal lung function and induce acute and chronic respiratory and cardiovascular illnesses [21][22][23][24][25][26][27].…”
Section: Characteristics Of Particulate Mattermentioning
confidence: 99%
“…Their ability to harbour environmental or workplace contaminants allows them to act as potential carriers of toxic or carcinogenic agents, such as polyaromatic hydrocarbons (PAHs) and per-and poly-fluoroalkyl substances, into the human airway and lung [11,20]. Once in the lungs, the particles and their contaminants can induce disease processes, resulting in pathophysiological changes that disrupt normal lung function and induce acute and chronic respiratory and cardiovascular illnesses [21][22][23][24][25][26][27].…”
Section: Characteristics Of Particulate Mattermentioning
confidence: 99%
“…It is a general agreement that PM affects the CV system through direct and indirect toxicity mechanisms ( 4 ). Indirect effects can be triggered by particles of every size, yet only fine and ultrafine PM can affect the heart and blood vessels directly as they enter the alveoli and pass into the systemic circulation ( 35 , 36 ). Another determinant of toxicity mechanisms is exposure duration.…”
Section: Cardiovascular Outcomes Of Particulate Matter: Lessons Learned From Epidemiology Studiesmentioning
confidence: 99%
“…Another indirect pathway of PM 2.5 action involves autonomic imbalance and activation of the sympathetic nervous system ( 35 , 48 ), which affects heart rate variability (HRV) necessary for proper CV function, as cardiac output may vary in response to signals from the autonomic nervous system. In one study ( 35 ), ceramic factory workers exposed to PM showed lower HRV and parasympathetic activity and an increased sympathetic activity.…”
Section: Cardiovascular Outcomes Of Particulate Matter: Lessons Learned From Epidemiology Studiesmentioning
confidence: 99%
“…Several epidemiological pieces of research have confirmed a substantial link between acute and chronic effects of air pollutants and CVDs (15)(16)(17)(18). In this respect, the WHO and several other public and private organizations have established health-based air quality guidelines for particulate matter and surface O 3 due to mounting evidence that these pollutants can cause a variety of adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%